The brood maturation of Hard-Lipped Barb (Osteochilus hasselti) with Technique of Implantation Using Human Chorionic Gonadotropin - dian azhar semidang; fia sri mumpuni; rosmawati rosmawati (Universitas Djuanda, 2018)
This research was aimed to know the best dosage of HCG (Human Chorionic Gonadotropin) for the brood maturation of hard-lipped barb. The experiment design has been conducted were completely random design with 4 treatments and 3 replications. The treatments are A (Control, without hormone), B (with HCG dosage of 250 IU), C (with HCG dosage of 500 IU), and D (with HCG dosage of 750 IU). The development of egg diameter, the success of spawning, fecundity, fertilization rate, and water quality (chemical and physical) have been evaluated. The results of research showed that treatment C gives the best results for the egg maturation of hard-lipped barb. Key words: Hard-lipped barb, HCG, the maturity of egg, fecundity